Analisis Pemanfaatan Aplikasi WhatsApp Dalam Pembelajaran Daring Di Sekolah Dasar - Yanuar, Ronald Felix; Wijanarko, Bagus Dwi (SISTEMA: Jurnal Pendidikan, 2021)
The COVID-19 pandemic that occurred in Indonesia also affected the learning process so that adjustments were needed to the learning process, one of which was online learning. In online learning, the WhatsApp application is often used during learning. This study aims to describe the use of the WhatsApp application in online learning in elementary schools, both in high and low classes. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observation and documentation. The data obtained were then analyzed by collecting data, reducing data, presenting data, and concluding the data. The results of this study indicated that the use of WhatsApp in learning was carried out in the high and low classes by utilizing the sharing features of videos, pictures, documents, and voice messages. Occasionally the video call feature was used in learning, but it was limited due to signal constraints. Apart from signal constraints, mastery of technology also hindered the development of learning. The recommendation given to improve the quality of learning is to collaborate with WhatsApp with other platforms and applications that support learning, and improve communication between teachers and parents in learning.